Antimicrobial activities of Terminalia chebula, Terminalia arjuna and Swertia chirayita against multidrug resistant Pseudmonas aeruginosa and comparison of their activities with locally available antibiotics. - Ashiquzzaman, D. M. (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.